Configuration morpho-lexicale du nom propre et propension à la lexicalisation - Montserrat Rangel Vicente (Lexis: Journal in English Lexicology)
Not every proper name is a proper noun. The acquisition of this status is, in principle, yet not always, devoid of visible traces. We postulate that some morpho-lexical configurations are more compatible than others with lexicalisation. This postulate is correlated with the hypothesis that the formal features of the signifier of proper noun may facilitate the identification of proper names which are the best candidates for lexicalisation. This hypothesis is examined through the analysis of a synchronic corpus of town/city and village names that shows the morphological heterogeneity of the lexical forms of that category. This analysis sheds light on the affinity of these toponymic lexemes with the monolexical configuration pure proper noun. It also reveals the existence of thresholds of maximum complexity in this type of lexemes, which vary according to the morpho-lexical category of their core. The analysis of the data also foregrounds the underestimated impact of opacity on the formal description of proper names and on their lexicalisation.